Meningkatkan Profesional Guru dengan Program Pendidikan Profesi Guru (PPG) - Iqbal Maulana; Nia Atikah Rahma; Namira Fitri Mahfirah; Wahyu Alfarizi; Ahmad Darlis (Journal on Education, 2023)
The development of professional teachers is protected by the Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers and Government Regulation of the Republic of Indonesia Number 74 of 2008 concerning Teacher Certification. Educator certification for teachers is obtained through professional education programs organized by tertiary institutions that have programs for procuring accredited education staff, both those held by the government and the community, which are then determined by the government. The research was conducted using a qualitative descriptive approach because it describes events. According to (Arikunto, 2006) "qualitative research is a certain tradition in social sciencethat fundamentally depends on observing humans in their own area, and dealing with people in their own language. Teachers in improving their professionalism must carry out their obligations and responsibilities to provide learning By providing material with the basic requirements, you must master structural material, concepts, and scientific mindsets that support the subjects being taught, if you don't fulfill them, you cannot teach, manage classes, conduct creative and innovative learning. Besides that,professional teachers must also achieve the required qualifications and competencies, build good peer relations and develop a work ethic or work culture that prioritizes high quality service. partners. Learning in the classroom includes material deepening, indicator formulation, syllabus preparation, presentations, peer teaching, formative tests. Furthermore, PPL in schools measures the mastery of competencies obtained in the classroom. Thus the PPG series aims to create professional teachers, prepare skilled teachers and establish four competencies.